The Effects of Media Exposure: Emmett Till's death in 1955 as the catalyst for the Civil Rights Movement - Kochevar, Chaz (My University, 2014)
This author's work looks to examine the aftereffects of the murder, trial and the publication of the Emmett Till?s photograph in 1955 through the newspapers of the time period and how Emmett Till shaped the future of American history through the Civil Rights Movement. The death of 14 year old Emmett Till in Money, Mississippi, as a news headline, could have just stayed within the locality of his murder and his story would have simply ended without much controversy. Yet, the people who witnessed his mangled face, saw his disfigured visage in Jet magazine and the Chicago Defender cried out in anguish on how such a gruesome act could have occurred in the United States. Emmett Till and his photograph become the catalyst for the Civil Rights Movement in America and forced African Americans of that time to realize the culture of racism, deference and racial violence in the South would never die out peacefully as many hoped it would. Till's death embodies the vision of the Civil Rights Movement and propels the movement not just in America, but garners worldwide attention to the racial divide occurring in the United States. This all occurring to the disbelief of the world who saw the true character of US domestic policy and society because of the exposure of his murder by the newsprint media.
Keywords: Till, Emmett, 1941-1955--Death and burial--Influence; Press--United States--Influence; Civil rights movements--United States--History; Racism--United States--Public opinion; Hate crimes--United States--Public opinion